Travel patterns of people with physical disabilities in attractions sector of Selangor’s tourism industry / Nurul Fatin Nabila Md Nafiah … [et al.] - Abd.Karim, Intan Farhana; Ahmad, Nurul Zamratul Asyikin; Shariff, Sharina; Ab Kadir, Mohd Sufian (2017)
This paper presents an insight on the impact of accessibility and attitudinal barriers encountered by travellers with physical disabilities towards their travel patterns in attractions sector of Selangor‘s tourism industry. The study is significant to improve accessible tourism in Malaysia as highlighted in The National Plan of Action for Persons with Disabilities (2007-2012), which was established to enhance awareness and create positive attitude, barrier-free environment, accessible transportation, access to information and defence from all forms of exploitation among people with physical disabilities. The research was conducted by using questionnaire to elicit accessibility barriers, attitudinal barriers and travel patterns of people with physical disabilities. 94 respondents were selected by using snowball sampling method, consist of people of physical disabilities who are 18 years old and above, lived in Shah Alam and at least once experienced the place of attractions in Selangor. Correlation and regression analysis were conducted to test the proposed model. The result indicates that both accessibility barriers and attitudinal barriers have significant relationship with travel patterns of people with physical disabilities. The result also shows that accessibility barriers have a greater influence on the travel patterns of people with physical disabilities than attitudinal barriers.